Impact of UV-C treatment and thermal pasteurization of grape must on sensory characteristics and volatiles of must and resulting wines. (15th February 2021) - Golombek, Patricia; Wacker, Michael; Buck, Nina; Durner, Dominik
Graphical abstract: Highlights: An UV-C dose of 2 kJ/L and pasteurization of must did not cause off-flavors. High UV-C doses (6 and 21 kJ/L) were found to be detrimental for wines. Only 21 kJ/L caused above-threshold concentrations of 2-aminoacetophenone. Changes in volatile compounds, such as terpenes and C13-norisoprenoids were observed. Linalool was relatively stable; β-damascenone was degraded by UV-C treatment. Abstract: UV-C treatment is a commonly known technique to inactivate microorganisms. The objective of this work was to investigate the impact of UV-C treatment of grape must on the sensory characteristics of the resulting wine and on the profile of volatile compounds of grape must and wine. Different UV-C doses were applied to Riesling must and compared with thermal pasteurization. The sensory off-flavor "ATA" and a content of 0.5 µg/L 2-aminoacetophenone were determined in the grape must and in the resulting wine after UV-C treatment with a high dose of 21 kJ/L. Sensory off-flavors did neither occur after thermal pasteurization nor after UV-C treatment with a dose of 2 kJ/L, which is sufficient for the inactivation of microorganisms. Minor changes in the volatiles' profiles of grape must and wine, involving e.g. terpenes and C13-norisoprenoids, occurred in musts treated with thermal pasteurization as well as with a UV-C dose of 2 kJ/L.